Exploring benefits and models of blended learning technology in modern professional training - Hrechanyk, Nataliia; Koval, Daria; Kovalchuk, Inna; Zinchenko, Lina (EDITORIAL PRIMMATE S.A.S, 2023)
The article shows the main ways of applying the mixed learning technology in the modern professional training of specialists. The purpose of the article is to find out the main ways of applying the technology of mixed learning in the modern professional training of specialists. The methodological concept provides a categorical and component analysis of the technology of mixed learning in the modern professional training of specialists in the following dimensions: philosophical, psychological, cultural, socio-pedagogical. The following methodological approaches were used in the article: sociosystemic, informational, synergistic, interdisciplinary, axiological, cultural, structural and functional and subject-activity. In connection with the digital transformation of education, we will distinguish three main components of mixed learning that can be implemented in a higher education institution, that is, in its information and educational environment (traditional learning (face to face); self-study learning; joint online - learning (online collaborative learning). The four basic models of mixed learning, which are discussed in the article, are the most popular (rotational model, flexible model, self-mixing model, virtualenriched model).

У статті показано основні шляхи застосування технології змішаного навчання при сучасній професійній підготовці фахівців. Метою статті є з’ясувати основні шляхи застосування технології змішаного навчання в сучасній професійній підготовці фахівців. Методична концепція передбачає категоріально-компонентний аналіз технології змішаного навчання в сучасній професійній підготовці фахівців у таких вимірах:філософський, психологічний, культурний, соціально-педагогічний У статті застосовувалися такі методологічні підходи: соціосистемний, інформаційний, синергетичний, міждисциплінарний, аксіологічний, культурологічний, структурно-функціональний та предметно-діяльнісний. У зв’язку з цифровою трансформацією освіти виокремимо три основні компоненти змішаного навчання, які можна реалізувати в закладі вищої освіти, тобто в його інформаційно-освітньому середовищі (традиційне навчання (face to face); самостійне навчання (self-study learning); спільне онлайн-навчання (online collaborative learning). Найпопулярнішими є чотири базові моделі змішаного навчання, які розглянуто у статті (ротаційна модель, гнучка модель, модель самостійного змішування, віртуально-збагачена модель).
Впровадження технології змішаного навчання в сучасну професійну підготовку фахівців
Keywords: technology of blended learning; professional training of specialists; digital transformation of education; information and educational environment; basic models of blended learning; технологія змішаного навчання; професійна підготовка фахівців; цифрова трансформація освіти; інформаційно-освітнє середовище; базові моделі змішаного навчання